Forever free - Morrow, Honoré, 1880-1940.; Frank and Virginia Williams Collection of Lincolniana (Mississippi State University. Libraries) (New York : A.L. Burt, William Morrow & Co., 1927)
99.0079 on back of front cover.
"Books consulted": pages 403-405.
Mode of access: Internet.
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Fiction; Fiction